Clinical Approaches to Conflicts Between Religious Values and Same‐Sex Attractions: Contrasting Gay‐Affirmative, Sexual Identity, and Change‐Oriented Models of Therapy. Issue 2 (October 2014) - Rosik, Christopher H.; Popper, Paul
<x xml:space="preserve">Abstract</x> The literature germane to the care of clients presenting for psychotherapy with conflicts between their sexual orientation and religious values typically addresses the topic from within a particular therapeutic approach. This article addresses the issue from a broader perspective that takes into account 3 different paradigms: gay‐affirmative therapy, sexual identity therapy, and change‐oriented therapy. The authors describe the 3 approaches, compare and contrast them across several different key dimensions of theory and practice, and identify some strengths and potential limitations of each approach for assisting clients who are attempting to navigate the resolution of their conflict.